2015
DOI: 10.1007/s00339-015-9557-6
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the effects of constructional elements on the mechanical behaviour of dragonfly wings

Abstract: Although wings of insects show a large variation in morphology, they are all made from a network of irregular veins interconnected through membranous areas. Depending on their shape, size, and position, wing veins are usually divided into three different groups: longitudinal veins, cross-veins and ambient veins. The veins together with the membrane and some other elements such as spines, nodus and pterostigma can be considered as the wing’s “constructional elements”. In spite of rather extensive literature on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…1A; see SI Appendix for details). This categorization of veins is similar to those used in previous studies (24,25).…”
Section: Resultssupporting
confidence: 58%
“…1A; see SI Appendix for details). This categorization of veins is similar to those used in previous studies (24,25).…”
Section: Resultssupporting
confidence: 58%
“…It has been shown that longitudinal veins, especially those situated close to the leading edge, dramatically enhance the stiffness of wings in the spanwise direction [ 2 , 5 , 8 ]. Numerical simulations indicate that the presence of longitudinal veins also improves the natural frequencies of both fore- and hindwings of dragonfly Orthetrum Sabina (Anisoptera, Libellulidae) approximately twofold, and therefore avoids structural failure due to resonance [ 9 ]. What are the underlying factors that cause the unique mechanical behaviour exhibited by insect wing veins?…”
Section: Introductionmentioning
confidence: 99%
“…Around veins thickened cuticle creates reinforcements, usually depicted as convex (above wing membrane as cuticular ridges in dorsal view) or concave (as cuticular grooves in ventral view), which cause wings corrugation (Kukalová-Peck 1978 ; Appel et al 2015 ). Until now, it has been believed that only veins strengthen the wings, but actually it is achieved thanks to the interaction of veins, wing membrane, and corrugations (Rajabi et al 2016a ).…”
Section: Introductionmentioning
confidence: 99%
“…A few other studies were recently carried out on wings of Orthoptera (Wootton et al 2000 ), Lepidoptera (O`Hara and Palazotto 2012 ), Coleoptera (Sun et al 2014 ), and Odonata (Appel et al 2015 ; Rajabi et al 2016a , b ), whose wings are bigger and more rigid than those of Sternorrhyncha.…”
Section: Introductionmentioning
confidence: 99%